If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 5x = 11 Reorder the terms: 5x + 3y = 11 Solving 5x + 3y = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 5x + 3y + -3y = 11 + -3y Combine like terms: 3y + -3y = 0 5x + 0 = 11 + -3y 5x = 11 + -3y Divide each side by '5'. x = 2.2 + -0.6y Simplifying x = 2.2 + -0.6y
| 3m-5+8m=17 | | 56+a+a^2=0 | | 56+a+a^2=0 | | 9/20=7.2/h | | 9/20=7.2/h | | 10(s-3)=-83 | | x-0.2x=498.20 | | x^6-6x^5+9x^4=0 | | (c-1)(-8c^2+c-5)= | | b/17.6=1/8.8 | | 5(n+3)=5 | | 7/9-7=-5 | | T=6-t | | 5d^2+20d+20=0 | | -1/8(4/5x-24)= | | 20.50x+395=1112.50 | | -1+5g=7g-9 | | fx=6x^5+3x^3+12x | | 24==v/3 | | -5n=-7-6n | | t/8.8=18/16 | | 9(n-12)=81 | | x^9-5x^8-24x^7=0 | | -4x-3(2x-16)=-32 | | 4(3n+1)=52 | | 6b=4b+10 | | 1/4(8x-4)= | | -4n^2-6n+9=9 | | 5x+40=15x+100 | | 2(2n+5)=18 | | 9-6c=-5c | | 63^2/6 |